KAJI KOMPUTASIONAL PENGARUH BEBAN DAN KEAUSAN TERHADAP KEKAKUAN BANTALAN ROL - Bintoro, Carolus; Bagiasna, Komang; Suharto, Djoko; Abidin, Zainal (Mesin, 2004)
This paper explores the study of numerical determination of roller bearing stiffness as a result of wear increment by using contact Hertzian method. This study is part of the research on the determination of roller bearing vibration response as a result of wear increment. In this paper, wear is assumed as diametral clearance, Cd, and force work in radial direction. Computational method shows that increasing wear causes the decrease of stiffness. The relationship between deflection and stiffness, radial load and stiffness as a function of Cd can be determined.